2020
DOI: 10.1136/tobaccocontrol-2020-056010
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities in secondhand smoke exposure before, during and after implementation of Quebec’s 2015 ‘An Act to Bolster Tobacco Control’

Abstract: BackgroundTo better understand whether tobacco control policies are associated with changes in secondhand smoke (SHS) exposure across socioeconomic groups, we monitored differences in socioeconomic inequalities in SHS exposure in households and private vehicles among youth and adults before, during and after adoption of Quebec’s 2015 An Act to Bolster Tobacco Control.MethodsUsing data from the Canadian Community Health Survey, we examined the prevalence of daily exposure to SHS in households and private vehicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 54 publications
(62 reference statements)
1
9
0
Order By: Relevance
“…From 204 full-text articles assessed for eligibility, 11 eligible studies were included in the qualitative synthesis (figure 1). 15,[25][26][27][28][29][30][31][32][33][34] No ongoing or unpublished studies were found.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From 204 full-text articles assessed for eligibility, 11 eligible studies were included in the qualitative synthesis (figure 1). 15,[25][26][27][28][29][30][31][32][33][34] No ongoing or unpublished studies were found.…”
Section: Resultsmentioning
confidence: 99%
“…30 Four of the 11 eligible studies did not meet EPOC criteria (figure 1). [31][32][33][34] Ten effect estimates from four studies evaluating the effects of smoke-free car policies on child TSE in cars could be meta-analysed given that they assessed the immediate effects of similar policies on the same outcome. 15,25,26,28 In the two-level meta-analysis of these estimates, smoke-free car policies were associated with an immediate risk reduction in child TSE in cars (RR 0•69, 95% CI 0•55-0•87; 161 466 participants; figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a Canadian study examining changes in secondhand smoke exposure before, during and after a 2015 population tobacco control measure that extended smoke-free laws found that among groups of different income and education levels, exposures among all groups decreased across time periods but the magnitude of inequalities in exposure did not change. 5 Given these persistent disparities, it is important to consider prioritising public health interventions that not only reduce smoking overall, but also contribute to reducing the disparities themselves. Smith et al 6 conducted a review on the equity impacts of population-level tobacco control interventions and found mixed results.…”
Section: Ruth E Malonementioning
confidence: 99%
“…For example, a study from Quebec found that SHS exposure in the home was nearly 5fold more common among youth in the lowest versus the highest income quin tiles. 29 Since public health orders to stay at home have likely increased the number of smokers who use tobacco indoors, it is probable that more individuals with low socioeconomic status have been and will continue to be exposed to SHS. Indoor smoking is especially concerning in multi unit housing, mostly populated by low income families, as smoke is carried in shared ventilation systems and therefore affects multiple dwellers.…”
Section: Covid-19 Undermines Tobacco Control Efforts and Exacerbates Tobacco-related Harm Among Socioeconomically Disadvantaged Groupsmentioning
confidence: 99%